Evaluasi Kinerja Guru SD Di Kabupaten Tabalong Menggunakan Metode Kuantitatif - Susanty, Susanty; Aslamiah, Aslamiah; Norhapizah, Norhapizah; Novitawati, Novitawati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
The goal of national education requires the optimal role of teachers as key elements in education. Therefore, teachers need to demonstrate strong performance. This study aims to identify the factors that significantly influence the improvement of teacher performance. The research employs a quantitative approach with a regression design. The study population consists of 1,820 teachers from 212 public elementary schools (SDN) in Tabalong Regency, with a sample drawn from this population for analysis. Data were collected using questionnaires and analyzed using descriptive statistical techniques and regression analysis. Regression analysis was utilized to examine both direct and indirect effects on teacher performance